2015
DOI: 10.1051/0004-6361/201425183
|View full text |Cite
|
Sign up to set email alerts
|

Narrowband selected high-redshift galaxy candidates contaminated by lower redshift [OIII] ultra-strong emitter line galaxies

Abstract: Context. Lyman-break galaxies (LBG) and narrowband (NB) surveys have been successful at detecting large samples of high-redshift galaxies. Both methods are subject to contamination from low-redshift interlopers. Aims. Our aim is to investigate the nature of low-redshift interlopers in NB Lyman-α emitters (LAE) searches. Methods. From previous HAWK-I NB imaging at z ∼ 7.7, we identify three objects that would have been selected as high-redshift LAEs had our optical data been one magnitude shallower (but still o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…We note that ELG30 has the highest equivalent width (EW) emission line of our sample, and that would suggest that it is an [Oiii] emitter since they in general have large EW (see e.g. Pénin et al 2015). Further insight into the redshift of ELG30 comes from Fig.…”
Section: Photometric Redshiftsmentioning
confidence: 72%
“…We note that ELG30 has the highest equivalent width (EW) emission line of our sample, and that would suggest that it is an [Oiii] emitter since they in general have large EW (see e.g. Pénin et al 2015). Further insight into the redshift of ELG30 comes from Fig.…”
Section: Photometric Redshiftsmentioning
confidence: 72%
“…Indeed, recent spectroscopic studies have shown that most of the interlopers that contaminated z ∼ 8 samples are at z ∼ 2 (e.g., Pénin et al 2014;Brammer et al 2013;Hayes et al 2012). For all objects, the best-fit SED has a significantly larger χ 2 and for three of them requires higher dust reddening than in the previous case.…”
Section: Sed-fittingmentioning
confidence: 90%
“…Alternatively, the Lyman break colors can also be mimicked by extremely strong emission lines in z = 1 − 3 star-forming galaxies (e.g., Atek et al 2011Atek et al , 2014avan der Wel et al 2011). In this class of galaxies the contribution of the emission line flux to the total broadband flux is about 25% on average and can reach 85% (Atek et al 2011) and can have important implications, not only for the high-redshift galaxy selection, but also on the age and stellar mass derived from SED fitting (Schaerer & de Barros 2009;Wilkins et al 2013;Schenker et al 2014a;Pénin et al 2015;Huang et al 2015). In our case, the contamination of one band can lead to an artificial Lyman break, because the faint continuum remains undetected blueward of the break.…”
Section: Sources Of Contaminationmentioning
confidence: 99%